ANALYSIS OF CAPTAIN VISIOND STORE'S MARKETING STRATEGY IN INCREASING CONSUMER PURCHASE INTEREST - Muhammad Hafisuddin; Sukaris Sukaris (Jurnal Interprof, 2026)
Objective: This study aims to analyze the marketing strategies of Captain Visiond Store in increasing consumer purchase interest. It addresses a significant research gap by exploring the integration of the marketing mix, digital marketing, and product exclusivity within the under-researched context of the local music merchandise industry. Methodology: Employing a descriptive qualitative approach, data were collected through in-depth interviews, observations, and documentation involving business owners and consumers. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, with credibility ensured through source and technique triangulation. Results: The findings reveal that consumer purchase interest is primarily driven by the synergy between product differentiation—specifically through unique visual designs and limited-edition scarcity and targeted digital marketing. The strategic utilization of social media and marketplaces not only expands market reach but also amplifies the perceived exclusivity and symbolic value of the merchandise, which are critical factors influencing purchase decisions alongside product quality and service responsiveness. Conclusion: The integration of emotional value (exclusivity and identity) with functional value (quality and digital accessibility) constitutes a highly effective marketing strategy for sustaining consumer interest in the creative merchandise sector. Limitations: The reliance on a single qualitative case study limits the generalizability of the findings across broader creative industry contexts. Contribution: Theoretically, this study enriches marketing literature by conceptualizing the role of product scarcity and digital engagement in niche creative markets. Practically, it provides a strategic blueprint for MSME actors to leverage product differentiation and digital ecosystems to build sustainable competitive advantages